Mattimeo - Jacques, Brian; Chalk, Gary (New York : Firebird, 2003)
Mattimeo, the son of the warrior mouse Matthias, learns to take up the sword and joins the other animal inhabitants of Redwall Abbey in resisting Slagar the fox and his band of marauders.
"First published in 1989 by Hutchinson's Children Books Ltd."--T.p. verso.
A tale of Redwall
Keywords: Mice -- Fiction; Animals -- Fiction; Fantasy